CT-Scan Findings of Patients Presented with Hepatic Mass attended at Tertiary Care Hospital in Bangladesh - Begum, Wahida; Hussain, Khondker Shaheed; Islam, Tariqul; Rupa, Sharmin Sultana (Journal of Current and Advance Medical Research, 2015)
Background: CT-scan findings give a well delineated impression on hepatic mass. Objective: The purpose of the present study was to observe the CT-scan findings of hepatic mass. Methodology: This cross sectional study was carried out in the department of Radiology and Imaging MMC in collaboration with the same department of BSMMU, DMC, Dhaka during the period of 1st January 2006 to 31st December 2007 to establish the usefulness of CT scan in the diagnosis of hepatic mass and its validity by determining sensitivity, specificity, PV, NPV, and accuracy. A total of 50 patients were admitted in the Department of Medicine and Department of Hepatobiliary of MMCH, BSMMU, and DMCH with the clinical diagnosis of fever, abdominal pain, anorexia, nausea/vomiting, loss of appetite, jaundice, weight loss and ascites. They were sent to the department of Radiology and Imaging and of respected hospitals for CT evaluation, confirmation and to see the extension for planning of proper management. Result: A total number of 50 hepatic mass patients were recruited in this study. CT findings of all patients showed 29 had lesions on right lobe, six patients had on left lobe and 15 patients had lesion on both lobe (p value <0.05). Among all patients 28 had multiple lesion, of them 71.4% was malignant and 28.6% was benign. On the other side 22 patients had solitary lesion, of them 36.4% was malignant and 63.6% was benign (p value <0.05). Among all malignant lesions 17 (60.7%) were hypodense, followed by 6 (21.4%) were isodense and 5 (17.9%) had mixed pattern of density. 12 (42.9%) patients of malignant diseases had ill-defined margin and 16 (57.1%) had well defined margin. 6 (27.3%) patients of benign lesions had ill-defined and 16 (72.7%) had well defined margin. No significant difference was observed. All malignant lesions (100%) and 77.3% benign lesions were enhanced after giving contrast. 16 (57.1%) malignant lesions were mildly enhanced, 10 (35.7%) were moderate and 2 (7.1%) were intensely enhanced. On the other side 8 (47.1%) benign lesions were mild, 35.5% were moderate and 3 (17.6%) were intensely enhanced. Conclusion: In conclusion hepatic mass is more common in right lobe of the liver of which multiple lesion is commonly found. Journal of Current and Advance Medical Research 2015;2(1):7-11 DOI: http://dx.doi.org/10.3329/jcamr.v2i1.22580